Accounting and cryptocurrency: analytical process in venezuelan companies (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2021)
Technology becomes a great catalyst in the evolution of business and commercial praxis, incorporating new ways of carrying out processes and procedures, including accounting. One of the technological issues that have been impacting business dynamics is related to cryptocurrencies. By virtue of this, this article aims to analyze the current situation of the accounting process related to Cryptocurrencies in Venezuelan companies, taking as a reference the IFRS and the Ba Ven NIF 12. This research was developed from the positivist paradigm, with a quantitative approach level descriptive, supported by a field study; the sample is made up of 68 accounting managers from companies geographically located in 4 states of the Bolivarian Republic of Venezuela. The results showed a diversity in the criteria of recognition, valuation, presentation and disclosure of the operations or holding of cryptocurrencies. It is concluded that there is evidence of high levels of non-compliance with the requirements of the regulations that govern the accounting process for this item at the national level (Ba Ven NIF No. 12). Highlighting the large number of entities that are not recognizing all the transactions or holding of cryptocurrencies in the accounting. Situation that excessively affects the integrity and reasonableness of the financial information that they would be presenting.
Keywords: cryptocurrencies; accounting; Venezuelan companies; Ba Ven NIF 12; NIIF